Plexiform Neurofibroma: A Case Report. Issue 6 (February 2016) - Tchernev, Georgi; Chokoeva, Anastasiya Atanasova; Patterson, James W.; Bakardzhiev, Ilko; Wollina, Uwe; Tana, Claudio
Abstract : Abstract: Plexiform neurofibromas represent an uncommon variant (30%) of neurofibromatosis type 1 (NF-1) in which neurofibromas arise from multiple nerves as bulging and deforming masses involving also connective tissue and skin folds. We report a rare case of a 30-year-old man who presented with a progressive facial deformity that began in early childhood. Skin examination also revealed multiple neurofibromas and café-au-lait macules on the trunk and arms. Histopathological examination on biopsy samples showed overgrowth of peripheral nerve components and connective tissue. Two diagnostic criteria for NF-1 (plexiform variant) were met, the patient did not accept to undergo genetic testing. Craniofacial MRI confirmed the presence of a deforming mass arising from the left side of his face giving homolateral eye dislocation. Surgery is the mainstay of the treatment. However, the patient expressed the preference to avoid surgery and chose to undergo clinical follow-up every 6 months. Diagnosis of plexiform neurofibromas is usually made clinically, especially if classical hallmarks of NF-1 are present. Therapy is surgical, aiming at resecting deforming masses and cancerous tissue when malignant transformation occurs.